2017
DOI: 10.7554/elife.30640
|View full text |Cite
|
Sign up to set email alerts
|

AKT isoforms have distinct hippocampal expression and roles in synaptic plasticity

Abstract: AKT is a kinase regulating numerous cellular processes in the brain, and mutations in AKT are known to affect brain function. AKT is indirectly implicated in synaptic plasticity, but its direct role has not been studied. Moreover, three highly related AKT isoforms are expressed in the brain, but their individual roles are poorly understood. We find in Mus musculus, each AKT isoform has a unique expression pattern in the hippocampus, with AKT1 and AKT3 primarily in neurons but displaying local differences, whil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
96
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(108 citation statements)
references
References 56 publications
(89 reference statements)
9
96
0
Order By: Relevance
“…The involvement of AKT signaling in LTP is well established (Bruel-Jungerman et al, 2009;Levenga et al, 2017). Indeed, the use of AKT inhibitors or ablation of Akt1 in mice impaired L-LTP, the long-lasting form of LTP whose maintenance is required for forming memories (Levenga et al, 2017). We demonstrate an LTP impairment in our ITSN1-LKO mice, suggesting that, at least in part, this may be a result of the negative effect that the lack of ITSN1-L has on the activation of AKT.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…The involvement of AKT signaling in LTP is well established (Bruel-Jungerman et al, 2009;Levenga et al, 2017). Indeed, the use of AKT inhibitors or ablation of Akt1 in mice impaired L-LTP, the long-lasting form of LTP whose maintenance is required for forming memories (Levenga et al, 2017). We demonstrate an LTP impairment in our ITSN1-LKO mice, suggesting that, at least in part, this may be a result of the negative effect that the lack of ITSN1-L has on the activation of AKT.…”
Section: Discussionsupporting
confidence: 49%
“…Although we demonstrated no change in MAPK/ERK signaling activity in ITSN1-LKO mice, we did find a decrease of 19% in the basal level of phosphorylated AKT in ITSN1-LKO hippocampal homogenates. The involvement of AKT signaling in LTP is well established (Bruel-Jungerman et al, 2009;Levenga et al, 2017). Indeed, the use of AKT inhibitors or ablation of Akt1 in mice impaired L-LTP, the long-lasting form of LTP whose maintenance is required for forming memories (Levenga et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies revealed that AKT and ERK activation were obviously attenuated in the brain of APP/PS1 mice, indicating that LEO can mediate these rapid kinase signaling pathways. Recently, both AKT and ERK signaling has been explained to help regulate the LTP, memory and synaptic plasticity [63][64][65]. Thus, we propose that LEO mediates AKT and ERK activation in the brain, which may contribute dramatically to its effects on the LTP, synaptic plasticity and memory of APP/PS1 mice.…”
Section: Agingmentioning
confidence: 81%
“…According to the results of the WB, the phosphorylation levels of ERK and CREB were obviously increased in the hippocampus in response to the administration of bee pollen extract. Another important molecule associated with learning and memory is Akt, which plays a role in LTP formation 41) and memory consolidation. 42) GSK-3β, a major substrate of Akt, is known to be an important regulator of neurogenesis and synaptic plasticity in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%